Studying the Influence of Orientation and Layer Thickness on the Physico-Mechanical Properties of Co-Cr-Mo Alloy Manufactured by the SLM Method - Adjamskiy, S.; Kononenko , G.; Podolskyi , R.; Baduk , S. (Science and Innovation, 2024)
Introduction. The additive manufacturing technologies have recently become more widespread in modern production, as they allow the quick and efficient manufacture of products with a unique geometry. Problem Statement. For the production of parts, it is necessary to use rational technological parameters that depend on the characteristics of the material and equipment for selective laser melting (SLM). Among the factors affecting the mechanical properties there are the sample orientation in the working chamberand the thickness of the working layer. Purpose. The purpose of this research is to study the effect of sample orientation in the direction of the X, Y, Z axes and layer thickness (40 and 20 μm) on the physical and mechanical properties of the Co-Cr-Mo alloy fabricated by the selective laser melting method. Material and Methods. All prototypes are made of Co-Cr-Mo alloy powder with a particle size of 10–45 μm. The samples are printed with layer thicknesses of 20 and 40 μm, with the use of an Alfa-150 3D printer manufactured by ALT Ukraine LLC. The samples for tensile tests are placed on the platform in horizontal (X and Y axes) and vertical (Z axis) positions. The tests to determine the mechanical properties have been carried out in accordance with ISO 6892:2019, on a PHYWE testing machine. The thermal expansion coefficient has been determined with the use of a DIL.A.802 dilatometer. Results. The dependence of the metaldensity at a constant thickness of the deposited layer of 40 and 20 μm and a distance between tracks of 0.1—0.12 mm has been established, and the rational conditionsfor manufacturing samples for tensile tests have been chosen. Conclusions. It has been established that a decrease in the intertrack distance contributes to the achievement of a density of 99.99% and an increase in the area of the rational printing conditions. It has been shown that the samples printed with different thicknesses of the working layer have different mechanical properties. When comparing samples made at different layer thicknesses and placed in the same direction, we have found that the temporary resistanceis the lowest for the vertical samples as compared with the horizontal ones in the X and Y directions.